Typifications in American and Australasian Rhynchospora sect. Pauciflorae (Cyperaceae) - Lima Alves, Karina De Nazaré; Thomas, William Wayt; Bittrich, Volker; Dos Santos Bragança Gil, André (Phytotaxa, 2024)
In this work, 17 lectotypifications are proposed for names related to Rhynchospora section Pauciflorae Kük. The lectotypifications are part of a nomenclatural revision of the section, which has not been revised since its creation by Kükenthal in 1949. Protologues and nomenclatural types were consulted online, in physical herbaria, or in libraries. These typifications are essential for the correct application of species names and synonyms in accordance with the principles of the International Code of Nomenclature for Algae, Fungi, and Plants.